The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1186/1471-2199-11-24
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis of the venom gland of the red-headed krait (Bungarus flaviceps) using expressed sequence tags

Abstract: BackgroundThe Red-headed krait (Bungarus flaviceps, Squamata: Serpentes: Elapidae) is a medically important venomous snake that inhabits South-East Asia. Although the venoms of most species of the snake genus Bungarus have been well characterized, a detailed compositional analysis of B. flaviceps is currently lacking.ResultsHere, we have sequenced 845 expressed sequence tags (ESTs) from the venom gland of a B. flaviceps. Of the transcripts, 74.8% were putative toxins; 20.6% were cellular; and 4.6% were unknown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 104 publications
(98 reference statements)
3
25
0
Order By: Relevance
“…Snake venom is frequently cited as being highly complex or diverse (Li et al, 2005;Wagstaff 48 et al, 2006;Kini and Doley, 2010) and a large number of venom toxin genes and gene 49 families have been identified, predominantly from EST-based studies of gene expression 50 during the re-synthesis of venom in the venom glands following manually-induced emptying 51 ("milking") of extracted venom (Pahari et al, 2007;Casewell et al, 2009;Siang et al, 2010;52 that lies outside of the proposed Toxicofera clade (Figure 1). We have also taken advantage 111 of available transcriptomes or RNA-Seq data for corn snake vomeronasal organ 112 (Brykczynska et al, 2013) and brain (Tzika et al, 2011), garter snake (Thamnophis elegans) 113 liver (Schwartz and Bronikowski, 2013) and pooled tissues (brain, gonads, heart, kidney, 114 liver, spleen and blood of males and females (Schwartz et al, 2010)), Eastern diamondback 115 rattlesnake (Crotalus adamanteus) and eastern coral snake (Micrurus fulvius) venom glands 116 (Rokyta et al, 2011;Rokyta et al, 2012;Margres et al, 2013), king cobra (Ophiophagus 117 hannah) venom gland, accessory gland and pooled tissues (heart, lung, spleen, brain, testes, 118 gall bladder, pancreas, small intestine, kidney, liver, eye, tongue and stomach) (Vonk et al,119 2013), Burmese python (Python molurus) pooled liver and heart (Castoe et al, 2011), green 120 anole (Anolis carolinensis) pooled tissue (liver, tongue, gallbladder, spleen, heart, kidney and 121 lung), testis and ovary (Eckalbar et al, 2013) and bearded dragon (Pogona vitticeps), Nile 122 crocodile (Crocodylus niloticus) and chicken (Gallus gallus) brains (Tzika et al, 2011), as 123 well as whole genome sequences for the Burmese python and king cobra (Castoe et al, 2013; 124 .…”
mentioning
confidence: 99%
“…Snake venom is frequently cited as being highly complex or diverse (Li et al, 2005;Wagstaff 48 et al, 2006;Kini and Doley, 2010) and a large number of venom toxin genes and gene 49 families have been identified, predominantly from EST-based studies of gene expression 50 during the re-synthesis of venom in the venom glands following manually-induced emptying 51 ("milking") of extracted venom (Pahari et al, 2007;Casewell et al, 2009;Siang et al, 2010;52 that lies outside of the proposed Toxicofera clade (Figure 1). We have also taken advantage 111 of available transcriptomes or RNA-Seq data for corn snake vomeronasal organ 112 (Brykczynska et al, 2013) and brain (Tzika et al, 2011), garter snake (Thamnophis elegans) 113 liver (Schwartz and Bronikowski, 2013) and pooled tissues (brain, gonads, heart, kidney, 114 liver, spleen and blood of males and females (Schwartz et al, 2010)), Eastern diamondback 115 rattlesnake (Crotalus adamanteus) and eastern coral snake (Micrurus fulvius) venom glands 116 (Rokyta et al, 2011;Rokyta et al, 2012;Margres et al, 2013), king cobra (Ophiophagus 117 hannah) venom gland, accessory gland and pooled tissues (heart, lung, spleen, brain, testes, 118 gall bladder, pancreas, small intestine, kidney, liver, eye, tongue and stomach) (Vonk et al,119 2013), Burmese python (Python molurus) pooled liver and heart (Castoe et al, 2011), green 120 anole (Anolis carolinensis) pooled tissue (liver, tongue, gallbladder, spleen, heart, kidney and 121 lung), testis and ovary (Eckalbar et al, 2013) and bearded dragon (Pogona vitticeps), Nile 122 crocodile (Crocodylus niloticus) and chicken (Gallus gallus) brains (Tzika et al, 2011), as 123 well as whole genome sequences for the Burmese python and king cobra (Castoe et al, 2013; 124 .…”
mentioning
confidence: 99%
“…Transcriptomic analysis of the venom gland of Bungarus flaviceps showed that 2.87% of the transcripts were of the A chain and 32.01% were of the B chain of b-bungarotoxin. This suggests that b-bungarotoxin is likely to be a major protein in the venom, and it is known to be the main lethal component (Siang et al, 2010). In addition, a cluster of Kunitz toxins similar to the B chain of b-bungarotoxin, but without the extra cysteine required for covalent interaction with the A chain, was also observed (Siang et al, 2010).…”
Section: Studying Venom Evolutionmentioning
confidence: 92%
“…This suggests that b-bungarotoxin is likely to be a major protein in the venom, and it is known to be the main lethal component (Siang et al, 2010). In addition, a cluster of Kunitz toxins similar to the B chain of b-bungarotoxin, but without the extra cysteine required for covalent interaction with the A chain, was also observed (Siang et al, 2010). As the cysteine residue (when present) is located on the C-terminal end of the mature protein, the addition or loss of such a residue can help lead to or negate (respectively) the formation of a dimer.…”
Section: Studying Venom Evolutionmentioning
confidence: 97%
See 1 more Smart Citation
“…44 Subsequently, reptilian NPs were puried from the venoms of Pseudocerastes persicus, 45 Oxyuranus microlepidotus, 46 Crotalus durissus cascavella (¼C. d. terricus), 47 Micrurus corallinus, 48 Bungarus avi-ceps, 49 and Agkistrodon halys blomhoffii (¼Gloydius blomhoffii blomhoffii). 50 Recently, NPs have also been identied in the venom glands of the Mexican beaded lizard (Heloderma horridum).…”
Section: Natriuretic Peptidesmentioning
confidence: 99%